(untitled) (International Journal of Islamic Business, 2022)
In today’s business world, the traditional ways of doing business are rapidly being replaced with online transactions. More and more companies realise that they need to digitalize their operation processes to keep abreast with the local and foreign competitors. This practice is no exception to zakat institutions in Malaysia when they must seize this technology evolution to ease the zakat payers in fulfilling the obligation as Muslim via online payment system. This study aims to identify the determinants affecting the intention to use online zakat payment among Muslim in Shah Alam, Selangor. A structured questionnaire is distributed to 300 Muslim respondents Muslim using a convenience sampling technique. The results of the estimated multiple regression show that perceived usefulness, perceived ease of use and security and privacy critical drivers of intention to use online zakat payment while no significant relationship was found between trust and amount of information to use online zakat payment. Thus, the empirical findings of this study provide a point of reference to zakat institutions to leverage the usefulness and ease of use of the online collection zakat system to increase zakat collections. Additionally, the institution must also beef up its security and privacy of users to alleviate the acceptance of online system usage.